Cardiovascular Actions and Therapeutic Potential of Tetramethylpyrazine (Active Component Isolated from Rhizoma Chuanxiong): Roles and Mechanisms. (23rd May 2016) - Guo, Ming; Liu, Yue; Shi, Dazhuo
Abstract : Tetramethylpyrazine (TMP), a pharmacologically active component isolated from the rhizome of the Chinese herb Rhizoma Chuanxiong (Chuanxiong), has been clinically used in China and Southeast Asian countries for the prevention and treatment of cardiovascular diseases (CVDs) for about fifty years. The pharmacological effects of TMP on the cardiovascular system have attracted great interest. Emerging experimental studies and clinical trials have demonstrated that TMP prevents atherosclerosis as well as ischemia-reperfusion injury. The cardioprotective effects of TMP are mainly related to its antioxidant, anti-inflammatory, or calcium-homeostasis effects. This review focuses on the roles and mechanisms of action of TMP in the cardiovascular system and provides a novel perspective on TMP's clinical use.